2018
DOI: 10.1590/0104-070720180000390016
|View full text |Cite
|
Sign up to set email alerts
|

Saberes Sobre Processo De Enfermagem No Banco De Leite Humano

Abstract: Objective: to analyze nurses' knowledge regarding the nursing process as an instrument for Nursing Care Systematization in the Human Milk Bank.Method: descriptive, exploratory, qualitative study carried out in the second quarter of 2015 in seven Human Milk Banks in the State of Espírito Santo. With this perspective, nine nurses working in the health service were interviewed. The data were submitted to thematic content analysis.Results: the nursing process can be considered an organizer of work in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
(17 reference statements)
0
6
0
7
Order By: Relevance
“…With regard to the content addressed in the selected videos, there was a significant number of explanations about the concept of the NP and the difference with the SNC, which can indicate doubts and/or disagreements regarding the real meaning of this term, although it is already defined in the literature as a structured methodological instrument that helps nurses to develop continuous patient care (1,2,4,5) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the content addressed in the selected videos, there was a significant number of explanations about the concept of the NP and the difference with the SNC, which can indicate doubts and/or disagreements regarding the real meaning of this term, although it is already defined in the literature as a structured methodological instrument that helps nurses to develop continuous patient care (1,2,4,5) .…”
Section: Discussionmentioning
confidence: 99%
“…The Nursing Process (NP) is a methodological instrument structured in five dynamic and interconnected stages (data collection, diagnosis, planning, interventions and Nursing assessment), which help nurses to develop the care provided to the patient in an organized manner, through critical thinking activities and the recording of essential information (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study developed in institutions in the state of Espírito Santo identified that actions taken with patients in a superficial way can disqualify the other stages of the nursing process ( 56 ) . On the other hand, a research carried out in Hungary has shown that empowered patients, identified as literate and trained, reported better health status compared to any other group of patients ( 57 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Importante dizer que a capacitação constante dos profissionais de saúde de modo a possibilitar o embasamento teórico, torna mais efetivas suas ações em prol do aleitamento Materno pois amplia os saberes e melhora a qualidade da assistência (Prates et al, 2016;Vasquez et al, 2015& Marchiori et al, 2018.…”
Section: Atuação Da Enfermagem Na Amamentaçãounclassified